Qualidade ambiental dos fragmentos florestais na Bacia Hidrográfica do Rio Jundiaí-Mirim entre 1972 e 2013 - Fengler, Felipe H.; Moraes, Jener F. L. de; Ribeiro, Admilson I. [UNESP]; Peche Filho, Afonso; Storino, Moises; Medeiros, Gerson A. de [UNESP] (Univ Federal Campina Grande, 2015)
The location of Jundiai-Mirim river basin, close to large urban centers and industrial parks, has contributed to the appreciation of their lands. Consequently, the region has an intense process of urbanization that resulted in an increasing environmental disturbance in the forest areas. Given the need to preserve existing natural vegetation, because the watershed is the source of water used to supply Jundiai, SP, this study evaluated changes in the environmental quality of the watershed forest fragments between 1972 and 2013. The environment quality was determined by evaluating nine indicators of environmental disturbance, obtained by techniques of Geoprocessing and integrated by Multicriteria Analysis. The results showed a constant tendency of deteriorating the environmental quality of natural vegetation between 1972 and 2013, attributed to the intense process of occupation of the watershed. It is concluded that: (a) urbanization and deforestation of natural vegetation were primarily responsible for changes in environmental quality; (b) there is a need to create public policies to preserve the natural vegetation in the watershed.

A localização da Bacia Hidrográfica do Rio Jundiaí-Mirim, próximo a grandes centros urbanos e parques industriais, tem contribuído para a valorização das suas terras; em consequência, a região apresenta intenso processo de urbanização, que resultou em um aumento crescente da perturbação ambiental nas áreas florestais. Dada à necessidade de manutenção da vegetação natural, visto que a bacia hidrográfica é a fonte da água utilizada no abastecimento de Jundiaí, SP, este trabalho avaliou as modificações na qualidade ambiental dos fragmentos florestais da bacia hidrográfica entre 1972 e 2013. A qualidade ambiental foi determinada por meio da avaliação de nove indicadores de perturbação ambiental obtidos através de técnicas de Geoprocessamento e integrados pela Análise Multicritério. Os resultados mostraram uma tendência constante de deterioração da qualidade ambiental da vegetação natural entre 1972 e 2013, atribuída ao intenso processo de ocupação da bacia hidrográfica. Concluiu-se que: (a) a urbanização e o desmatamento da vegetação natural foram os principais responsáveis pelas alterações na qualidade ambiental; (b) existe a necessidade de criação de políticas públicas para a preservação da vegetação natural do manancial.
Environmental quality of forest fragments in Jundiai-Mirim river basin between 1972 and 2013
Keywords: Multicriteria analysis; Environmental disturbance; Land use and occupation; Remote sensing